Design of a 200kW electric powertrain for a high performance electric vehicle (2016)
With the purpose of designing the electric powertrain of a high performance electric vehicle capable of running a quarter mile in 10 seconds, firstly it is necessary to calculate the required energy, torque, and power in order to size and select the suitable storage components and electric motors. Secondly, an assessment of the powertrain arrangement is needed to choose the best internal configuration of the vehicle and guarantee the highest efficiency possible. Finally, a design of the power conversion stages, specifically the DC-DC converter that interfaces the storage unit with the electric motors, is required as well. This paper shows the energy calculation procedure based on a longitudinal dynamic model of the vehicle and the selection method of the storage components and motors needed for this application, as well as the design of two 100kW interleaved boost converters with coupled inductors. In addition, a novel operation of the interleaved boost converter is proposed in order to increase the efficiency of the converter. As a result, the designed converter achieved a power density of 24,2kW/kg with an efficiency of 98 %, which was validated by experimental tests of a low power prototype.